The therapeutic effect of Nigella sativa L. seeds oil on experimentally infected rabbits with hepatic coccidiosis: Rafid, K. Ali1 ; Rajiha A. S. Al-Naimi1 ; Houida H. Abed2 and Eman H. Al-Tace2 - Ali, Rafid K. (The Iraqi Journal of Veterinary Medicine, 2015)
The present study was carried out to investigate the therapeutic effect of Nigella sativa seeds oil emulsion as against Eimeria stiedae experimentally infected rabbits. After isolation of local E. stiedae strain from infected gallbladders, a total of 90 local rabbits (6-8 weeks age) and body weighing (750-1000 gm) were used. They were divided into 6 groups as follow: Group: 1 uninfected and untreated (control group), Group: 2 infected (untreated) with 10,000 sporulated oocysts of E. stiedae, Group: 3 uninfected and given 200mg/kg B.W. N. sativa L. oil emulsion, Group: 4 infected with 10,000 sporulated oocysts of E. steidae. and treated with N. sativa L. oil emulsion of 200 mg/kg B.W on day 16, post infection, Group: 5 uninfected and given 400 mg/kg B.W N. sativa L. oil emulsion, Group: 6 infected with 10,000 sporulated oocysts of E. stiedae. and treated with N. sativa L. oil emulsion of 400 mg/ kg B.W on day 16, post infection. Fecal sample were examined for oocyst count (16 days post infection) at each period of experiment (10, 20 and 30 days) 5 animals for each group were sacrificed, and specimens for liver, were excised for histopathological examination. The E. stiedae infected group showed deleterious pathological changes in infected livers. Both treated doses of N. sativa had significant anticoccidial activities as reflected by reduced fecal oocysts shedding and remarkable improvement of liver tissue histopathology. This improvement include restoration of normal hepatic architecture and increase of the binucleated hepatocytes, disappearance of hemorrhage between the hepatic lobules, formation of foreign body granulomas and reduction in the various stages of the parasites and oocysts in the bile ducts .The result showed that changes more rapid when animals were treated with 400 mg/ kg/ B.W of N. sativa seeds oil emulsion than when treated same emulsion at dose 200 mg/ k.g/ B.W without side effects. From the results obtained in the present study N. sativa seeds oil emulsion was safe without side effects and the dose 400 mg/kg/B.W was more effective against E. stiedae infection than dose 200 mg/kg/B.W which may be recommended for use as adjuvant therapy in clinical practices.